A resource-aware control approach to vehicle platoons under false data injection attacks. (December 2022) - Yang, Fan; Gu, Zhou; Hua, Lingzhi; Yan, Shen
Abstract: Wireless vehicle-to-vehicle communication brings inevitable imperfections. This work simultaneously addresses the resource utilization and security issues for a vehicle platoon. Inspired by the modeling of denial of service attacks, a novel queuing model is constructed to depict false data injection attacks. A switched event-triggered mechanism is proposed to optimize network resources. The transmission rate can be actively reduced when the system is under malicious attacks. Then, a unified error system is established, where string stability is interpreted as global exponential stability. By using a proper Lyapunov function, a co-design approach is developed for closed-loop controllers and event-triggering parameters, with which the vehicle platoon can maintain a small safety distance and resist the negative impacts of cyber attacks. Finally, the proposed methods are verified by a virtual vehicle platoon. Highlights: Resource utilization and security issues are simultaneously investigated for vehicle platoons. A novel queuing model depicts false data injection attacks. A switched event-triggered mechanism adaptively saves network resources. String stability is interpreted as asymptotic stability.